Analysis of the Correlation between Operating Cash Flows and Dividend Changes in Tehran Stock Exchange (TSE) - Mohammad Hossein Setayesh (Shahid Bahonar University of Kerman, 2011)
The purpose of this study is to investigate the relationship between operating cash flows and dividend changes. This is applied to the impact of operating cash flows on the lagged dividends and the net operating income. The statistical population was taken from listed companies in Tehran Stock Exckange, TSE, and a sample of 136 listed companies was surveyed. Despite the importance of operating cash flows in evaluating the cash dividend policies, the results showed no significant relationship between them. In order to re-examine the impact of operating cash flows on cash dividend policies, the sample is divided into three sub-samples with regard to growth level values. Again there were no significant relationship between dividend changes and operating cash flows of companies. This shows that there may be some other factors that create changes in the cash dividend policies.